The Role of the Program Indonesia Pintar in Increasing School Participation Among Underprivileged Children - Fatiroh, Eti; Mutmainnah; Bibi , Tahira; Fauzi, Hairul (CV. Zabags Qu Publish, 2025)
Education is the main foundation for the development of competitive human resources, but access to equitable education is still a serious challenge for children from underprivileged families. Economic inequality results in low school participation among vulnerable groups, although the government has launched the Smart Indonesia Program (PIP) as an affirmative strategy to encourage education sustainability through cash assistance. This study aims to describe the implementation of PIP and analyze its role in increasing school participation of underprivileged children. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation from PIP recipients, parents, principals, and program managers in the research area. The results show that PIP contributes positively to the sustainability of education through the reduction of economic barriers, but its effectiveness is still influenced by the validity of recipient data, delays in the distribution of funds, and social support in the surrounding environment. This research emphasizes the importance of synergy between education policy, technical supervision, and community participation in supporting poor children to continue to access formal education. These findings make conceptual contributions to social justice theory and enrich practical understanding of the implementation of more inclusive and contextual educational assistance programs.